2018
DOI: 10.1364/jocn.10.000b58
|View full text |Cite
|
Sign up to set email alerts
|

Location-Aware Energy Efficient Virtual Network Embedding in Software-Defined Optical Data Center Networks

Abstract: To overcome the Internet ossification, network virtualization has been proposed as a promising method because of its advantages (e.g., on demand and efficient resource allocation). Virtual network embedding (VNE) is one of the main challenges for network virtualization. Energy costs of servers in data centers (DCs) are major contribution to power consumption in information and communication technology (ICT). Therefore, VNE should consider both acceptance ratio and power consumption. In this paper, a mixed inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Unlike previous research, we address in this paper an intra and inter cloud resources Parallel and Proactive VNE (PGTR-PPVNE), considering various energy types' availabilities in intra and inter cloud levels. We compared all our simulated results with the whole benchmark algorithms mentioned in [11]. The following section describes in detail our proposed solution architecture aiming to maximize REs utilizations, then network and DCs' servers total power efficiency.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike previous research, we address in this paper an intra and inter cloud resources Parallel and Proactive VNE (PGTR-PPVNE), considering various energy types' availabilities in intra and inter cloud levels. We compared all our simulated results with the whole benchmark algorithms mentioned in [11]. The following section describes in detail our proposed solution architecture aiming to maximize REs utilizations, then network and DCs' servers total power efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…In this later layer, we address a Parallel and Proactive Virtual Network Embedding (PPVNE) sorting the total power efficiency of the whole network components and DCs' servers. Inspired by [11] and our previous complete survey study [12], we propose a mathematical MILP model maximizing total power efficiency in both DCs and inter cloud multi-domain networks components in the SD-ODCN architecture. Contributions in this paper are synthesized as follows: -After instantiating Virtual Network Requests (VNRs) in the SP layer, each user requiring multi-services VNRs at a fixed time stamp may benefit from a parallel and distributed processing in a timely manner.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive simulation results demonstrated that the proposed method (E-LB-VNE) can reduce the energy consumption and improve the load balance of substrate network while slightly deteriorating the long-term average revenue, acceptance ratio, and revenue to cost ratio. Again, to minimize total power consumption (router port, EDFAs, OXCs, transponders and servers in DCs) in software-defined optical data center networks (OCDN), study in [51] proposes a global topology resource (GTR) reflecting the selection of each node and link in the substrate network. Based on this GTR method, two energy-efficient VNE algorithms were composed to improve the performance in the scalability of requests and topology.…”
Section: Virtual Network Embedding (Vne)mentioning
confidence: 99%
“…To determine the power quality of a power grid, many different performance indexes have been proposed [20][21][22][23]. In the adding lines problem, we needed a metric to indicate the voltage profile.…”
Section: Power Mileagementioning
confidence: 99%